Crisis communication strategies in social networking sites: The case of the rise in fuel prices - Godoy Martín, Francisco Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The economic situation in Spain during the first half of the year 2022 was characterised by a rise in prices which had a major effect on fuel prices. Within the framework of crisis communication management, this article discusses the strategies followed by the main companies in the fuel sector on Twitter by using the content analysis method. The results show that silence was the main position adopted by these organizations. This reflects the absence of proactive crisis management.